Enhanced NH3-SCR activity of Sb-V/CeO2-TiO2 catalyst at low temperatures by synthesis modification - Huong Thi Danh; Kumar, Pullur Anil; Jeong, Young Eun; Ha, Heon Phil (SPRINGER, 2016)
In this work, the synthesis of Sb-V/CeO2-TiO2 catalyst was modified by controlling pH with the addition of monoethanolamine solution. All the catalysts were systematically investigated for NO (x) reduction with NH3 at different reaction conditions and then characterized by XRD, BET-surface area, X-ray photoelectron spectroscopy, NO-TPD, NH3-TPD, and H-2-TPR. This modified synthesis method for the Sb-V/CeO2-TiO2 catalyst exhibited noticeably higher NO (x) reduction activity at low temperatures (< 250 A degrees C). H-2-TPR revealed an increase of reducible species for the modified catalyst at basic pH, followed by neutral pH and acidic pH, respectively. High activity of the catalyst synthesized at basic pH was persistent for NO (x) reduction with time that was confirmed by the time on stream durability test under SO2 and water. The Ce 3d XPS spectra of spent catalyst synthesized at basic pH explains the gradual decrease in activity due to the decrease of Ce4+ to Ce3+ ratio by the formation of sulfates.
Keywords: RAY PHOTOELECTRON-SPECTROSCOPY; MIXED OXIDES; REDUCTION; NOX; NH3; CERIA; SO2; SCR; REACTIVITY; SULFATION